Field determination of nitrate in seawater using a novel on-line coppered cadmium column: A comparison study with the vanadium reduction method - Wenhan Niu; Hongliang Li; Xiaochen Guo; Jianfang Chen; Xiaolai Shi; Yong Zhu (Frontiers in Marine Science, 2023)
Nitrate is the main form of dissolved inorganic nitrogen, playing an important role in both marine biogeochemical research and water environment management. In this work, the most commonly used coppered cadmium column was modified and a novel on-line Cu/Cd column with a spiral structure coupled with a de-bubbling device and syringe-type filter was developed. With the advantages of convenience, portability, stability, and high reduction efficiency, the interference of air bubbles in the column could easily be avoided. Based on the classic Griess reaction, a simple reverse flow injection system coupled with a novel Cu/Cd column and custom-made flow cell was established for the field spectrophotometric determination of nitrate in seawater. The effects of certain reaction parameters—including the reagent concentration, flow rate, length of the Cu/Cd column, and salinity—were investigated, optimized, and compared with pure water, with an approximate 9% increase in the sensitivity of seawater samples. This method exhibited a detection limit of 0.03 μmol/L, with a relative standard deviation of 0.6%, and the working range was 20 μmol/L before dilution. Compared to the referred vanadium reduction method based on the same flow system, the proposed method showed significant advantages including sensitivity and reproducibility. No significant difference was observed between the analytical seawater sample results obtained by the proposed and reference methods. Furthermore, the proposed method was validated by the first class of National Certified Reference Materials and successfully applied to the nitrate determination of Wenling coastal seawater (Zhejiang, China).